2011
DOI: 10.1002/arch.20432
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cloning and characterization of two nicotinic acetylcholine receptor β subunit genes from Apis cerana cerana

Abstract: Nicotinic acetylcholine receptors (nAChRs) mediate fast cholinergic synaptic transmission in the insect nervous system and are important targets for insecticides. In this study, we identified and characterized two novel β subunit genes (Accβ1 and Accβ2) from Apis cerana cerana. Homology analysis indicated that Accβ1 and Accβ2 possess characteristics that are typical of nAChR subunits although Accβ2 was distinct from Accβ1 and the other nAChR subunits, due to its unusual transmembrane structure and uncommon exo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
13
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 33 publications
4
13
0
Order By: Relevance
“…Our results demonstrated that pea aphid nAChR subunits were differentially expressed, first between developmental stages, as previously demonstrated in Drosophila and Apis cerana cerana [35], [37], [38], and also according to the neonicotinoid exposure. Neonicotinoid sensitivity could then be dependent on either physiological status and/or environmental conditions in the pea aphid.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Our results demonstrated that pea aphid nAChR subunits were differentially expressed, first between developmental stages, as previously demonstrated in Drosophila and Apis cerana cerana [35], [37], [38], and also according to the neonicotinoid exposure. Neonicotinoid sensitivity could then be dependent on either physiological status and/or environmental conditions in the pea aphid.…”
Section: Discussionsupporting
confidence: 85%
“…Moreover, recent studies demonstrated that nAChR subunit expression level was associated to neonicotinoid sensitivity [34], [35]. For example, a decrease in Accβ1 and Accβ2 subunit expression in the Asiatic honey bee Apis cerana was described after IMI exposure [35]. Our results also demonstrated that neonicotinoid toxicity was associated with specific nAChR subunit regulation.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…It is known that different nAChR sub-types have different pharmacological properties [42]. Thus, species could differ in their sensitivity to specific neonicotinoid compounds by having differential composition and populations of nAChR sub-types [43,44], or by differential responses in gene expression of nAChR subunits to pesticide exposure [45,46].…”
Section: Discussionmentioning
confidence: 99%
“…Imidacloprid and its metabolites act by binding to nicotinic acetylcholine receptors (nAChR) on honey bee neurons23. In A. cerana , imidacloprid binds to a nAChR receptor24. Imidacloprid consequently exerts a broad suite of sublethal neural effects: brain cell death25, impaired motor function2627, reduced food uptake28, decreased foraging29, diminished hive entrance activity30, reduced predator avoidance31, impaired navigation back to the nest3233, and compromised learning34.…”
mentioning
confidence: 99%